Academic Dishonesty on Students: What is the Role of Moral Integrity and Learning Climate? - Mamang Efendy; Rahma Kusumandari; Meininda Rhivent Norhidayah; Emilia Nur Aini Putri (Journal of Educational, Health and Community Psychology, 2023)
Academic dishonesty is a global problem that occurs in various parts of the world. Cases of academic dishonesty that are growing throughout the world are a serious concern for every country because they have a big impact on moral violations and other bad social behavior. This research aims to find out whether there is a relationship between moral integrity and academic dishonesty in students, and whether there is a relationship between learning climate and academic dishonesty in students. This research uses a correlational quantitative approach using 3 psychological scales as measuring tools, namely the academic dishonesty scale, the moral integrity scale and the learning climate scale which is adapted from previous researchers with good psychometric quality. The subjects in this research were 320 students from various levels throughout Indonesia who were taken using snowball sampling technique. Data analysis used the Pearson correlation test to answer hypothesis 1 and the Spearman correlation test for hypothesis 2 because of the two variable is not linear. The results of this research show that moral integrity has proven to be significant as a predictor of academic dishonesty behavior in students, however the research results found that there is no significant relationship between learning climate and academic dishonesty. The results of this research provide unexpected new findings that creating a positive learning climate alone is not enough to reduce the rate of academic dishonesty among students.